Effect of cimetidine and ranitidine on drug induced damage to gastric epithelial cell monolayers in vitro. Issue 10 (October 1989) - Romano, M; Razandi, M; Ivey, K J
Abstract : The effect of the H2 blockers cimetidine and ranitidine on drug induced damage to gastric cell monolayers has been evaluated in conditions independent of systemic factors and their anti-acid properties. Monolayers of mucous cells from a human cell line MKN 28, obtained from a human gastric adenocarcinoma, have been studied. Cell damage has been assessed qualitatively by trypan blue dye exclusion test and quantitatively by 51Cr release assay. Cimetidine and ranitidine significantly protected cultured cells against damage induced by sodium taurocholate decreasing taurocholate induced 51Cr release by 36% (p less than 0.001) and 28% (p less than 0.01), respectively. Cimetidine was also protective in concentrations lower than ranitidine. This protection was not prevented by the prostaglandin synthesis inhibitor indomethacin nor by the sulph-hydryl blocker N-ethylmaleimide. Incubation with cimetidine and ranitidine did not increase the production of PGE2 by cultured cells nor did it affect the cellular level of sulph-hydryl compounds. Cimetidine and ranitidine did not afford protection against damage induced by indomethacin and ethanol. Cimetidine in a concentration of 10 4M increased ethanol induced damage significantly. In conclusion (1) cimetidine and ranitidine protect gastric cells against taurocholate induced damage in vitro, independently of their anti-acid effect; (2) this protection is not mediated by prostaglandin E2 or sulph-hydryl compounds; (3) cimetidine and ranitidine do not protect gastric cells against damage induced by indomethacin and ethanol.